EDUCATIONAL ACTION AT SCHOOL FOR ELEMENTARY SCHOOL STUDENTS ABOUT HEART, STRUCTURE AND FUNCTIONING (CIPEEX, 2025)
EDUCATIONAL ACTION AT SCHOOL FOR ELEMENTARY SCHOOL STUDENTS ABOUTHEART, STRUCTURE AND FUNCTIONING Sarah Brandão DominguesMarta Isadora de Araújo  Jonathan de Almeida SoaresLuciana Caetano FernandesUniversidade Evangélica de Goiás - UniEVANGÉLICA    The objective of this study is to document the experiences of a workshop addressing the importance of the heart for human body structure and functioning, within the scope of a university extension project. The project involved 304 students in the sixth and seventh years of elementary school, aiming to improve student’s knowledge concerning the heart structure and functioning. In order to achieve this objective, interactive lectures, scavenger hunts and a heart model were given so that the target audience could associate the interactive model with the real organ, with the intention of understanding its structure and operation. The initiative was divided into three stages: initial assessment through a pre-test with 10 questions, which revealed the students' prior knowledge on the subject was very low when compared with what would be expected of students on this stage at school. In the second stage, medical students gave lectures in a panel discussion, listing cardiac structures using a demonstrative piece so that students could interact better with the dynamics of classes. And finally, in the third stage, the students were organized in small groups to participate in a contest with 20 questions related to the content of the lectures, in order to evaluate the knowledge acquired by them and the effectiveness of the project of health education, with a satisfactory result as there were very few errors. The initiative proved to be of great importance in allowing the improvement of knowledge of medical students who gave these lectures while they sought more knowledge about the structure and functioning of the heart, seeking to communicate the theme with the daily life of elementary school students, using simple language as tool, combined with accessible and interactive methodology, which helps to improve comprehensive medical training and social commitment to the community. The extension action was a unique experience for both elementary school students and medical students, who needed to develop ways to improve communication with the population in order to achieve their objectives. Thus, the tests applied proved that the project achieved its purpose of providing guidance on the heart, its structure and functioning. That way, it is very clear the relevance of continuing these health education initiatives to promote an increased knowledge about this vital structure, the heart.Keywords:  heart; structure; health education; medical students.
Keywords: heart; structure; health education; medical students